2020
DOI: 10.1016/j.mtphys.2020.100203
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected band gap increase in the Fe2VAl Heusler compound

Abstract: Knowing the electronic structure of a material is essential in energy applications to rationalize its performance and propose alternatives. Materials for thermoelectric applications are generally smallgap semiconductors and should have a high figure of merit ZT. Even if the Fe2VAl Heusler compound has a decent ZT, its conductive nature (semimetal or semiconductor) is not yet clarified especially at low temperature. In this paper, we focus our DFT calculations on the effect of temperature on the bandgap of Fe2V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
(48 reference statements)
1
12
1
Order By: Relevance
“…This picture of Anderson-localised states close to the Fermi level also reconciles many other peculiar properties of this compound, e.g. metallic thermodynamic and photoemission data in spite of semiconductorlike transport properties 20 , negative magnetoresistance 29 , anomalous Hall effect 30 etc., which have been an ongoing discussion over the past three decades 14,20,31 .…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…This picture of Anderson-localised states close to the Fermi level also reconciles many other peculiar properties of this compound, e.g. metallic thermodynamic and photoemission data in spite of semiconductorlike transport properties 20 , negative magnetoresistance 29 , anomalous Hall effect 30 etc., which have been an ongoing discussion over the past three decades 14,20,31 .…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…8 Quite recently, a further remarkable observation was made from DFT calculations: an opening of the band gap, driven by Al/V antisite occupations, which increases with temperature. 18 Antisite defects in the crystal structure of Fe 2 VAl will have an effect on physical properties, involving transport properties as well. From DFT calculations, Bandaru and Jund 19 demonstrated that the antisite defects Al V , Al Fe and V Al have the lowest formation enthalpies, thus being the most probable ones.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be seen as two combined Al V and V Al antisite defects. Since their formation energy is equal to 0.34 eV [16], they are the most likely thermally activated defects as shown in experiments [17] and simulations [16] and thus can be formed during annealing at high temperature T > 800 °C. Moreover, in our previous study [16], we showed that by taking Al/V inversions and temperature effects into account, the disagreement between the experimental and calculated band gap of Fe 2 VAl at high temperature (400 -800 K) can be reduced, indicating that inversions are probably present in experimental samples.…”
Section: Lattice Thermal Conductivity Of Fe 2 Val and Role Of Al/v Inversionsmentioning
confidence: 86%
“…To answer the first question, the present work considers the role of Al/V inversions in calculating the lattice thermal conductivity of Fe 2 VAl. We have shown in a previous theoretical study [16] that Al/V inversions (a combination of Al V and V Al antisite defects) are the most probable defects to form at high temperature. Experimentally, even strictly stoichiometric Fe 2 VAl samples most likely contain a sizable concentration of Al V and V Al antisite defects, which depends on their thermal history (for instance their annealing temperature when T > 800 °C) since at T = 1080 °C, Fe 2 VAl undergoes an order-disorder transition (second order) where 50 % of V and 50 % of Al atoms mix on their respective crystallographic sites [17].…”
Section: Introductionmentioning
confidence: 81%